Creativity and innovations in Nigerian academic libraries: Implications for library development (2012)
In the 21st century, the dominant driver in library and information services is rapid technological advancement involving several technologies including mobile applications and social media. Committed to assisting teaching, learning, research and community services and enhancing the best possible use of these libraries, many academic libraries in Nigeria have creatively and innovatively improved upon service delivery using a variety of ways and approaches. The aim of this paper is to discuss the phases of development which two of these libraries — the Kenneth Dike Library, University of Ibadan and the University of Lagos Library have undergone. The paper also highlights the products and services as well as the approaches that the librarians have adopted in meeting the ever changing needs of their clients. This paper is informed by the personal experience of the authors who had actively participated in projects that brought about the changes.